Spatial protection of nature in the light of the threats of upcoming decades - Tomiałojć, Ludwik (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
We live in a period of “global revolution” , when we have to start to act ina different way from models of the past millennia. The effects of overabundance of peopleand excessive consumption by some of them, such as: change of climate, pollution of theenvironment, destruction of biotopes, extinction of species etc., force us to modify the tasksand methods o f nature protection. It becomes urgent to treat equivalently active (manipulative)protection and traditional passive (preservational) conservation, as well as ex situ and in situprotection, although this attitude leads to various problems.Spatial protection requires counteraction against new threats based on novel concepts(such as e.g. minimal viable population, m etapopulational model etc.) and unifying thecreation of a netw ork of protected areas with moderate exploitation of natural resourcesoutside them. An adjustm ent of distribution, size and internal variation of protected areas tothreats arising from predicted changes in natural conditions is required. The necessity ofreintroducing new species and of reconstructing vanished biotopes has been justified, as wellas the need to carry out nature protection on a landscape scale, also in areas which areexploited economically, but there is also a need to hinder the invasion of alien species. Allthis requires an equal treatment of nature protection tasks in the realisation of proecoiogicalpolicy of the State.